2022
DOI: 10.3390/bs12080275
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Exposure and Left-behind Children’s Tobacco and Alcohol Use: The Roles of Deviant Peer Affiliation and Parent–Child Contact

Abstract: The public has always been concerned about the problem behaviors of children and teenagers (such as cigarette and alcohol use), especially among disadvantaged groups (e.g., left-behind children in China); in the current information era, left-behind children’s use of social media also has increasingly expanded, which has diverse effects on their adaptation. Accordingly, the present study examined the association between exposure to relevant content on social media and left-behind children’s tobacco and alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…First, rural left-behind adolescents are minors in rural areas whose parents or guardians cannot accompany them because they are away for extended periods for work, business, farming, or other reasons, and they are forced to live alone or with their grandparents, neighbors at home, or relatives [ 60 ]. Generally, such adolescents are cared for by grandparents or other relatives, have more severe emotional neglect problems, and face multiple risks and challenges, such as psychological problems, physical health problems, and fewer educational opportunities [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, rural left-behind adolescents are minors in rural areas whose parents or guardians cannot accompany them because they are away for extended periods for work, business, farming, or other reasons, and they are forced to live alone or with their grandparents, neighbors at home, or relatives [ 60 ]. Generally, such adolescents are cared for by grandparents or other relatives, have more severe emotional neglect problems, and face multiple risks and challenges, such as psychological problems, physical health problems, and fewer educational opportunities [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regular and positive contact between parents and left-behind children can promote parent–child relationships and reduce adverse effects. One study reported that parent–child contact protected left-behind children from tobacco and alcohol use 32. Mobile phones and various communication apps, such as WeChat and WhatsApp, have made it easier for migrant parents to keep in touch with their children back home.…”
Section: How To Solve the Problem Of Left-behind Childrenmentioning
confidence: 99%
“…One study reported that parent–child contact protected left-behind children from tobacco and alcohol use. 32 Mobile phones and various communication apps, such as WeChat and WhatsApp, have made it easier for migrant parents to keep in touch with their children back home. Frequent parent–child interactions can foster emotional bonds between parents and children and meet their emotional needs, thus reducing their negative emotions.…”
Section: How To Solve the Problem Of Left-behind Childrenmentioning
confidence: 99%
“…It may cause great harm to adolescents’ health and adaptation—tobacco and alcohol use cause brain damage [ 2 ], poor academic performance [ 3 , 4 ], and aggressive behaviors [ 5 ] among adolescents. Therefore, its influencing factors have been the focus of researchers, among which peer relationship, especially deviant peer affiliation, has received attention [ 6 , 7 , 8 , 9 ]. This is because the influence of peer relationships surpasses other interpersonal relationships (such as parent–child relationships) and becomes one of the main factors affecting adolescents’ psychological and behavioral development [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, adolescents who originally did not smoke or drink alcohol may use tobacco and alcohol to close the gap and enhance their relationships with their deviant peers as a result of their interactions with them [ 27 ]. Furthermore, extensive evidence showed that deviant peer affiliation can affect alcohol and tobacco use among adolescents [ 6 , 7 , 8 , 9 ]. Thus, we hypothesized that deviant peer affiliation is positively associated with adolescent tobacco and alcohol use (Hypothesis 1).…”
Section: Introductionmentioning
confidence: 99%